Online services in teaching the Kazakh language as a foreign language - Nurzhanova, Aisulu; Baltagul Ospanova, Zhanar Suinzhanova, Zhanat Yergubekova,; Barkibayeva, Rmkul (Opción, 2020)
The article is about the implementation peculiarities of online services in teaching Kazakh language as a foreign language via comparative qualitative research methods. As a result, the research done in terms of this article extensively analyzes three educational platforms suggested for learners work and discussion, benefit of an online service which was chosen as the most effective and comfortable one in teaching Kazakh as a foreign language to language learners, and the strengths over other platforms. In conclusion, the use of ICT can enhance the effectiveness of the learning process and increase the involvement of foreigners in learning the language.